THE EFFECT OF THE ROME I REGULATION UPON PARTIES CHOICE OF NONSTATE LAW AND AMIABLE COMPOSITION IN ARBITRATION - Ababneh, Ala Aldin Mohammad; Al Hawamdeh, Ahmed Mohammad (جامعة المنصورة - كلية الحقوق, 2012)
The study aims to explore the effect of the Rome I Regulation upon parties' choice of non-state law or resolving the dispute ‘amiable composition’ in arbitration. Although it is argued by some commentators that these concepts cannot be applied to arbitration as an effect of the Regulation, nevertheless the study concludes that parties are allowed to choose non-state law to be applied and arbitrators are obliged to follow their choice. Although the Rome I regulation does not have any effect in choice of law rules in arbitration, this does not mean that the arbitration system is completely free from the Rome I Regulation. For example, arbitrators like judges are obliged to apply the mandatory rule of law within Europe.
Keywords: اللوائح التنظيمية -- القانون الدولي -- التحكيم الدولي -- روما